(untitled) (Journal of Computational Mathematics, 1987)
A modified Calahan method for parabolic equations with time-dependent coefficients is presented. It is shown that the convergence order is O(h^r+1+k^3) while the convergence order obtained in [1] for a standard Calahan method is only O(h^r+1+k^2).